Constitutional history of modern Britain since 1485 - Keir, David Lindsay (London, 1969)
The author traces the constitutional development of Britain and the British Commonwealth by describing the structure and working of the main organs of government during the successive stages of their growth. He interprets their evolution with reference tu the political and social conditions and the currents of thought and opinion by which it has been determined. He also shows how government has been conducted by living and changing communities of men sharing a common political tradition.
Keywords: Constitutional history- Britain